Assess The Level Of Smooth And Stable Of The Suspension When Convert From Mechanical Suspension To Air Suspension - Huu Huy Nguyen; Lanh Thanh Le; Thoi Le Nam (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
This report illustrates the result of calculation of the level of smooth and stable of the bus when converting suspension from mechanical suspension to air suspension. The mechanical vibrations of the automobile in moving process includes: amplitude, frequency, acceleration, .... These factors may affect the safety of goods and the human state in the bus. This result also shows the great strengths of air suspension than mechanical suspension so that the requirement of smooth level in movement is guaranteed which is a good condition to rise the safety of goods in the bus, maitain human health, reduce physical fatigue and psychological tireness of drivers and passengers.